Women in local politics: Insights from Nanggroe Aceh Darussalam, Indonesia - Alex Alex; Nasiwan Nasiwan; Abdillah Abdillah; Mutiah Haris (Faculty of Social and Political Science, Universitas Airlangga, 2023)
Aceh is a region that is still strongly implementing Islamic law and a patriarchal political culture. The purpose of this study is to examine the dynamics of women’s participation in local Acehnese politics. This study uses a qualitative-exploratory method with a literature study on the dynamics of women’s participation in local Acehnese politics. The results of this study indicate that post tsunami 2004 and the 2005 Helsinki MoU agreement had an impact on openness for Acehnese women in the process of becoming members of the legislature, which is currently experiencing obstacles due to structural, socio-cultural, religious issues, ideology, and the dominance of local Aceh political party elites by men. This has greatly affected the representation of women in Aceh’s politics governance, even though during the 2009 to 2019 election year the representation of women in Aceh’s politicsgovernance has experienced a fairly good trend of increasing. However, what is being pursued is not the number that increases every year, but the process of fulfilling women’s political rights in Aceh. The conclusion of this study is the importance of holding a commitment to fight for women’s rights so that they are accommodated in public policies that are sensitive to women’s interests, not only as a complement to the quota for women’s representation in politics-government.